Proposals to improve adherence to immunomodulatory therapies in patients with multiple sclerosis - E. Arroyo; M. González; C. Grau; C. Arnal; M. Bujanda; P. de Castro; L. Grau; M. Martínez; C. Ramo; V. Sánchez; O. Sánchez-Soliño (Neurología (English Edition), 2010)
Introduction: The objective of this work was to assess the factors identified in the Global Adherence Project (GAP) in disease-modifying therapy (DMT) in patients with multiple sclerosis (MS) and to propose measures directed at improving adherence. It was proposed to prepare questionnaires to detect patients at risk of non-adherence before and during the follow-up. Methods: Two meetings were held by Spanish researchers involved in the GAP project. Factors associated with non-adherence were grouped in therapy-, patient-, disease- and health care professional-related factors. Four working groups were created. Each group studied one individual, factor, taking into account the stages of diagnosis, management and administering treatment, follow-up and discontinuation or change of treatment. A draft of proposals and tools (questionnaires) was agreed. Results: Patients should be provided with summaries of treatments, in a positive and simple way, and have time to discuss any doubts. Questionnaires should be given to patients at the start of treatment and during follow-up, so that individual characteristics can be assessed in order to monitor their adherence and act accordingly. Patients should be instructed in the management of the most common adverse reactions. Conclusion: Therapeutic education to improve adherence to treatments and identification of non-adherent patients is recommended. We propose 2 questionnaires, initial and follow up, to stratify patients depending on their adherence Resumen: Introducción: El objetivo de este trabajo fue evaluar los factores, identificados en el estudio global de adherencia (GAP), asociados con la adherencia a los fármacos inmunomoduladores (IMA) en pacientes con esclerosis múltiple (EM) para proponer medidas directas que mejoren la adherencia. Se propuso elaborar cuestionarios que permitiesen detectar, previamente y durante el seguimiento, a pacientes en riesgo de falta de adherencia. Métodos: Se celebraron dos reuniones con investigadores participantes en el estudio GAP en España. Se agruparon factores relacionados con la no adherencia asociados al tratamiento, paciente, enfermedad y profesionales de la salud. Se formaron 4 grupos de trabajo. Cada grupo trabajó de forma individual sobre un factor teniendo en cuenta el diagnóstico de la EM, manejo y aplicación de la medicación, seguimiento y retirada o cambio de tratamiento. Se acordó un borrador de propuestas y herramientas (cuestionarios). Resultados: Se debe proporcionar a los pacientes un resumen de las características de los tratamientos, de modo positivo y simple, así como tiempo para plantear dudas. La entrega de cuestionarios a los pacientes al inicio del tratamiento y durante el seguimiento para evaluar características individuales puede ayudar a conocer su grado de adherencia y actuar en consecuencia. Los pacientes deben ser educados en la identificación y el manejo de las reacciones adversas. Conclusiones: Se recomienda la educación terapéutica para favorecer la adherencia a los tratamientos e identificar a los pacientes no adherentes. Proponemos 2 cuestionarios, de inicio y de seguimiento, para poder estratificar a los pacientes en función de su adherencia. Keywords: Adherence, Multiple sclerosis, Immunomodulators, Palabras clave: Adherencia, Esclerosis múltiple, Inmunomoduladores